Don't sell out safety: a call to preserve risk evaluation and mitigation strategies to reduce harm to patients and the public in the U.S. Issue 1 (December 2016) - Worthy, Stacey
Abstract Background As medicines are becoming more targeted and complex in the U.S., ensuring patients' safe use of medications with known dangerous risks is critical for public health and safety. Therefore, the Risk Evaluation and Mitigation Strategies (REMS) program is more important than ever. The REMS programs mandates that manufacturers utilize tools to manage known or potential serious risks (e.g., death, severe birth defects, prolonged hospitalization) associated with certain drugs while still making these medications available to patients with unmet medical needs. Yet, recently federal policy makers have proposed legislation to force manufacturers to sell medications with known serious risks in a manner that weakens the medications' REMS programs. Methods The author reviewed U.S. legislation, statutes, case law, government agency policies and guidelines, scholarly articles, and news stories published between January 1, 2004 and December 1, 2015 and provided legal and policy analysis. Results REMS are necessary to make medications with known severe risks available to certain patient populations for whom treatment may not be available otherwise. Conclusion In order to ensure that proper safety measures are preserved and medications with known risks are not diverted to parties who will not follow safety requirements, legislation should not be passed to require a forced sale of drugs subject to REMS with restricted distribution for bioequivalence testing purposes. Generic manufacturers must be held to the same REMS safety standards as brand manufacturers. Systems currently in place adequately balance risk and safety.